A Study on Physico-chemical Properties and Nutritional Profile of an Indigenous Cultivar - Black cumin (Nigella sativa L.) (International Journal of Food and Nutritional Sciences, 2022)
Objective: The present study was aimed to investigate the physico-chemical properties evaluation, proximate analysis and minerals profile of Nigella sativa L. (AN-1 variety) seeds.Methods: The physico-chemical properties, proximate analysis and minerals evaluation of black seeds were performed by following the standard methods. Results: Physico-chemical properties of seeds; color, odor, taste, size and shape of seeds, weight of seeds, bulk density, tapped density and seed coat content was determined. Hydration properties including hydration capacity, hydration index and swelling capacity were also evaluated. In proximate analysis, it was found that black seeds contain moisture (7.06%), crude protein (18.67%), crude fat (45.09%), crude fiber (7.33%), ash (4.33%) and total carbohydrates (17.51%). The results of mineral analysis showed the presence of minerals like Ca (2.63µg/ml), K (1.94 µg/ml), Zn (1.24 µg/ml), Cu (0.31 µg/ml), Mg (0.30 µg/ml). The findings indicated the presence of an appreciable content of nutrients and minerals, which has the potential to satisfy the nutritional requirements of the population. Therefore, these kinds of medicinal seed spices should be studied in future.